Consequences of the electrogenic function of the phagocytic NADPH oxidase - Rada, Balázs K (The Royal Society, 2005)
NADPH oxidase of phagocytic cells transfers a single electron from intracellular NADPH to extracellular O(2), producing superoxide [Image: see text] [Formula: see text] , the precursor to several other reactive oxygen species. The finding that a genetic defect of the enzyme causes chronic granulomatous disease (CGD), characterized by recurrent severe bacterial infections, linked [Image: see text] [Formula: see text] generation to destruction of potentially pathogenic micro-organisms. In this review, we focus on the consequences of the electrogenic functioning of NADPH oxidase. We show that enzyme activity depends on the possibilities for compensating charge movements. In resting neutrophils K(+) conductance dominates, but upon activation the plasma membrane rapidly depolarizes beyond the opening threshold of voltage-gated H(+) channels and H(+) efflux becomes the major charge compensating factor. K(+) release is likely to contribute to the killing of certain bacteria but complete elimination only occurs if [Image: see text] [Formula: see text] production can proceed at full capacity. Finally, the reversed membrane potential of activated neutrophils inhibits Ca(2+) entry, thereby preventing overloading the cells with Ca(2+). Absence of this limiting mechanism in CGD cells may contribute to the pathogenesis of the disease.